THE INFLUENCE OF ORGANIZATIONAL CULTURE AND RISK AWARE CULTURE ON OPERATIONAL RISK MANAGEMENT - Brita Maria Cahya Krisyanti; Rakesh Sitepu; Djoko Adhi Saputro; Fanniza Putri Dwita; Daniel Gobai (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Operational risk management plays a strategic role in supporting the sustainability of activities and the achievement of organizational goals. The effectiveness of risk management depends not only on the existence of formal systems and procedures, but is also significantly influenced by the organizational culture and the risk awareness culture that shapes the attitudes and behaviors of individuals in the organization. This study aims to examine the influence of organizational culture and risk-aware culture on operational risk management in general. The research method used is a literature study of national and international scientific journals published in the period 2019–2025 and is relevant to the topic of organizational culture, risk culture, and risk management practices. The results show that a strong organizational culture, reflected through consistent leadership, shared values, accountability, and open communication, makes a positive contribution to the implementation of operational risk management. In addition, a risk-aware culture encourages the formation of proactive behaviors in identifying, reporting, and controlling operational risks. These findings confirm that the success of operational risk management relies heavily on internalizing organizational cultural values and strengthening risk awareness at all levels of the organization. Thus, the integration of organizational culture and risk-aware culture is the main foundation in building effective and sustainable operational risk management.